ULK1 Signaling in the Liver: Autophagy Dependent and Independent Actions - Rajak, Sangam; Raza, Sana; Sinha, Rohit Anthony (Frontiers in Cell and Developmental Biology, 2022)
Liver is the primary organ for energy metabolism and detoxification in the human body. Not surprisingly, a derangement in liver function leads to several metabolic diseases. Autophagy is a cellular process, which primarily deals with providing molecules for energy production and maintains cellular health. Autophagy in the liver has been implicated in several hepatic metabolic processes such as lipolysis, glycogenolysis and gluconeogenesis as well as to provide protection against drugs and pathogens, and its deregulation is associated with the development of non-alcoholic fatty liver disease (NAFLD), acute-liver injury and cancers. The process of autophagy is synchronized by the action of autophagy family genes or autophagy (Atg) genes that perform key functions at different steps. The uncoordinated-51-like kinases 1 (ULK1) is the proximal and the only kinase member of the Atg family that plays a critical role in both general and organelle selective autophagy. Interestingly, ULK1 actions on hepatic cells may also involve some autophagy-independent signaling. In this review, we provide a comprehensive update of ULK1 mediated hepatic action involving lipotoxicity, acute liver injury, cholesterol synthesis and HCC involving both its autophagic and non-autophagic functions.